Pengaruh Tingkat Religiusitas Dan Pemasukan Mahasiswa Terhadap Minat Bersedekah Mahasiswa Jurusan Ekonomi Syariah Angkatan 2023 - Humairoh, Ghaida; Amalia, Alda; Alghifari, Muhammad Fariz; Salsabila, Mutiara (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2024)
This study aims to examine whether the level of religiosity and student income influence the interest in giving alms among students majoring in Islamic Economics, Class of 2023, at Sultan Ageng Tirtayasa University. This qualitative study uses multiple linear regression analysis. The population in this study were students majoring in Islamic Economics, Class of 2023, at Sultan Ageng Tirtayasa University. The sample used in this study was 82 students majoring in Islamic Economics, Class of 2023, at Sultan Ageng Tirtayasa University, Banten. The results of the study indicate a positive influence between the level of religiosity and student income on the interest in giving alms, as evidenced by the results of the partial correlation test which showed a significance of 0.001 <0.05 and at a value of 3.321>1.664. There is a positive influence between the level of religiosity of students majoring in Islamic economics Class of 2023 at Sultan Ageng Tirtayasa University on the interest in giving alms as evidenced by the results of the correlation test significance of 0.65> 0.05 and the calculated t value of 1.992> 1.267. There is a positive influence between the level of income of students majoring in Islamic economics Class of 2023 at Sultan Ageng Tirtayasa University on the interest in giving alms as evidenced. The results of the study also show that there is a positive and significant influence between the level of religiosity and income of students on the interest in giving alms of students majoring in Islamic Economics Class of 2023 at Sultan Ageng Tirtayasa University which is stated with a significance value of 0.209 <0.05.